Implementasi Konsep Quality Home Care Dalam Meningkatkan Kesehatan Gigi Anak Disabilitas di SLB Kota Banda Aceh - Fitriani, Fitriani; Rahayu, Eka Sri; Nurhaida, Nurhaida; Reca, Reca; Salfiyadi, Teuku (PT. Riset Press International, 2024)
Children with special needs, such as those with Down syndrome, often face challenges in their dental growth and health. Common issues include cavities, misaligned teeth, and gum disease. Difficulties in maintaining oral hygiene independently further exacerbate these conditions. Given the risk of caries that can affect a child's development and the lack of parental knowledge about dental health, early prevention through understanding and parental involvement becomes crucial. Observations at the special education school (SDLB) revealed that 63% of the children experienced dental caries, and their average oral hygiene was rated poorly with a score of 2.6. This data indicates a condition that falls short of expectations relative to government health standards. Children with intellectual disabilities often struggle to learn self-care skills and require assistance both at home and at school. In this context, parents play a central role in teaching these skills to their children. This community service program was conducted using a descriptive method, targeting both children and their mothers as respondents. Data analysis was performed using a univariate approach. The dental nursing care services were planned over 5 days, totaling 40 effective hours with three visits. Interventions included educating mothers about maintaining oral health, simulating and demonstrating proper tooth brushing techniques, and applying the concept of quality home care for parents. This included guidance, monitoring, and providing dental care that can be performed at home as preventive measures. The results of this community service activity indicated an increase in parents' knowledge and skills in caring for their children's dental health. This positively impacted the oral hygiene of the children at SDLB and fostered a change in parental behavior in supporting their children to brush their teeth independently.